ASPECTE ALE EVALUĂRII ÎNTREPRINDERII - Ulian, Galina (CEP USM, 2009)
This article is dedicated to the aspects of business valuation: the needed of valuation, steps of valuation process, and new methodologies of business valuation.
Keywords: evaluarea întreprinderii; evaluarea afacerii